Elaboration of Nanostructured Levan-Based Colloid System as a Biological Alternative with Antimicrobial Activity for Applications in the Management of Pathogenic Microorganisms - Vitalijs Radenkovs; Anda Valdovska; Daiga Galina; Stefan Cairns; Dmitrijs Jakovlevs; Sergejs Gaidukovs; Ingmars Cinkmanis; Karina Juhnevica-Radenkova (Nanomaterials, 2023)
Considering the documented health benefits of bacterial exopolysaccharides (EPSs), specifically of bacterial levan (BL), including its intrinsic antimicrobial activity against certain pathogenic species, the current study concentrated on the development of active pharmaceutical ingredients (APIs) in the form of colloid systems (CoSs) containing silver nanoparticles (AgNPs) employing in-house biosynthesized BL as a reducing and capping agent. The established protocol of fermentation conditions implicating two species of lactic acid bacteria (LAB), i.e., Streptococcus salivarius K12 and Leuconostoc mesenteroides DSM 20343, ensured a yield of up to 25.7 and 13.7 g L−1 of BL within 72 h, respectively. An analytical approach accomplished by Fourier-transform infrared (FT-IR) spectroscopy allowed for the verification of structural features attributed to biosynthesized BL. Furthermore, scanning electron microscopy (SEM) revealed the crystalline morphology of biosynthesized BL with a smooth and glossy surface and highly porous structure. Molecular weight (Mw) estimated by multi-detector size-exclusion chromatography (SEC) indicated that BL biosynthesized using S. salivarius K12 has an impressively high Mw, corresponding to 15.435 × 104 kilodaltons (kDa). In turn, BL isolated from L. mesenteroides DSM 20343 was found to have an Mw of only 26.6 kDa. Polydispersity index estimation (PD = Mw/Mn) of produced BL displayed a monodispersed molecule isolated from S. salivarius K12, corresponding to 1.08, while this was 2.17 for L. mesenteroides DSM 20343 isolate. The presence of fructose as the main backbone and, to a lesser extent, glucose and galactose as side chain molecules in EPS hydrolysates was supported by HPLC-RID detection. In producing CoS-BL@AgNPs within green biosynthesis, the presence of nanostructured objects with a size distribution from 12.67 ± 5.56 nm to 46.97 ± 20.23 was confirmed by SEM and energy-dispersive X-ray spectroscopy (EDX). The prominent inhibitory potency of elaborated CoS-BL@AgNPs against both reference test cultures, i.e., Pseudomonas aeruginosa, Escherichia coli, Enterobacter aerogenes, and Staphylococcus aureus and those of clinical origin with multi-drug resistance (MDR), was confirmed by disc and well diffusion tests and supported by the values of the minimum inhibitory and bactericidal concentrations. CoS-BL@AgNPs can be treated as APIs suitable for designing new antimicrobial agents and modifying therapies in controlling MDR pathogens.